Pojęcie wypadku przy pracy rolniczej – uwagi de lege ferenda - Puślecki, Damian (WYDAWNICTWO NAUKOWE UNIWERSYTETU IM. ADAMA MICKIEWICZA, POZNAŃ, 2011)
The aim of this paper was to make an attempt at the determination of a new concept of an occupational accident in agriculture. The current definition of such an accident, despite its broad scope and introduced changes, does not sufficiently include accident events, which may occur in agriculture and does not facilitate their qualification in the post-accident proceedings. In conclusion the author proposed a simplification of the definition and adopting its following form: “An occupational accident in agricultural activity is a sudden event caused by an external factor, causing damage to the organism or death, if it occurred in the course of performance of agricultural activity or remained in connection with the performance of such activity. An accident covered by protection needs also to include such events, which occurred on the way to the site of performance of such activity or when returning from that site, if the travel was not interrupted by an unnecessary break.”

Lo scopo di questo lavoro è un tentativo di determinare la nuova nozione di infortunio sul lavoro in agricoltura. L’attuale definizione dell’infortunio, nonostante la sua ampiezza e le modifiche apportate, non include nel modo dovuto gli incidenti che possono verificarsi in agricoltura e non facilita la loro qualificazione nel procedimento seguente all’incidente. In conclusione, l’Autore propone di semplificare la definizione e di assegnarle la seguente dicitura: „Un infortunio sul lavoro nella attività agricola è un evento improvviso determinato da cause esterne, il quale provoca le lesioni dell’organismo o la morte, se esso si è verificato durante lo svolgimento delle attività connesse all’attività agricola o in relazione con lo svolgimento di queste attività. Come infortunio coperto dall’assicurazione devono essere considerati anche gli eventi verificatisi durante il percorso di andata e ritorno dall’abitazione al posto di lavoro (svolgimento delle attività), salvo le eventuali interruzioni non giustificate”.
THE CONCEPT OF AN OCCUPATIONAL ACCIDENT IN AGRICULTURE – DE LEGE FERENDA REMARKS
LA NOZIONE DI INFORTUNIO SUL LAVORO IN AGRICOLTURA – OSSERVAZIONI DE LEGE FERENDA